Multifunctional Gold-Silica Composite Platform Towards Comprehensive Cancer Therapy - Tew, Lih Shin (2018)
Incomplete cancer cells eradication with sole treatment of chemotherapy or radiation therapy was commonly reported. Therefore, gold nanoshells-based nanodevices have gained interests owing to the tuneablity of the localised surface plasmon resonance (LSPR) from visible to near infrared (NIR) wavelength, which is favourable for biomedical applications. In this work, gold nanoshell (GNS), of which has mesoporous silica nanoparticle core (MSN) filled doxorubicin (DOX) as well as polyethylene glycol (PEG) and AS1141 aptamer (Apt) at the outer layer (DOX-GNS-PEG-Apt), was designed for two photon laser-triggered chemo- and photothermal therapy. The results show 30.00 2.91 % of doxorubicin (DOX) was loaded into MSNs. The synthesised GNS was thenanalysed by UV-Vis spectroscopy and TEM, of which 4:1 ratio of K-gold to MSN-NH2 seed produced ideal gold thickness. The nanoparticles with a complete gold coverage on mesoporous silica core were observed. Based on the TEM and Energy Dispersive X-Ray spectroscopy (EDX) data, the gold film synthesised via grow-mediated process was approximately 10 – 15 nm thickness. Then, two photon excitation (TPE) was introduced to evaluate the efficacy of photothermal therapy (PTT) alone and the synergistic chemo-photothermal therapy. Deformation of GNS was evidenced by the blue shift of plasmon resonance peak from 800 to 570 nm and the morphology of the GNS after TPE was further confirmed with TEM. According to the in vitro study, DOX-GNS-PEG-Apt positive selectively bound to MDA-MB-231 cells (cancerous) but not MCF-10A cells (non-cancerous).